Implementation of Digital Entrepreneurship for Generation Z at Vocational School - Setiyawan, Renita; Ulfatun, Titik (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
This study aims to describe the implementation of digital entrepreneurship as well as supporting and inhibiting factors for Generation Z at SMK Negeri 1 Purwodadi. This research uses a qualitative approach with a case study design. Data collection techniques through observation, interviews, and documentation. Data was obtained from 10 11th-grade students in Accounting and Financial Institutions, Marketing, Culinary, and two entrepreneurship teachers. The data analysis techniques used are data collection, data reduction, data presentation, drawing conclusions, and verification. The implementation of digital entrepreneurship at SMK Negeri 1 Purwodadi is structured through entrepreneurial learning and practice. There are several supporting and inhibiting factors that exist in the implementation of digital entrepreneurship at SMK Negeri 1 Purwodadi. Supporting factors include the implementation team, parental support, and awareness of the importance of digital technology. Meanwhile, inhibiting factors include students' lack of interest in digital entrepreneurship, limited internet access, and fear of failure.